Tata Kelola Pemanfaatan Teknologi Informasi Melalui Digitalisasi Hasil Pertanian dalam Upaya Meningkatkan Penjualan Produk di Kecamatan Cikancung - Tiris Sudartono; Yulia Listianti; Ratnanto Aditiarno; Dian Candra Fatiha; Wiwi Warsiati; Kasino Martowinangun; Oscar Rachman; Kartika Legistari (Institut Riset dan Publikasi Indonesia (IRPI), 2023)
Abstract Digital Marketing is an effective and efficient means of promoting and marketing producer products because it can reach consumers very easily and quickly. The people of Cikancung Sub-district, Bandung Regency, who mostly make their living from the agribusiness sector, need to be introduced to the Digital Marketing system through direct counselling to the community, especially farmers, because the methods used by farmers so far still use traditional methods. Extension on the optimisation of Digital Marketing in Cikancung Sub-district aims to make farmers change the pattern of marketing agricultural products from traditional patterns to digitalisation methods. This counselling is considered important so that farmers can increase the quantity of sales of agricultural products in a wider range of markets. Based on the results of extension activities on extension participants in Cikancung District, it can be concluded that in promoting and marketing agricultural products, they still use traditional patterns that are local with limited reach. Interactive dialogue occurred between the presenter of the material and the participants, which showed the participants' enthusiasm for the material presented. Thus it is suggested that in addition to the proactivity of farmers, it is hoped that the participation of the Regional Government can more intensively assist farmers in promoting the agricultural products of the Cikancung District community, Bandung Regency. Keyword: Information Technology,Digitalisation,Sales Products,